Promising Flavonoids Against Neuropathic Pain: Their Mechanism And Therapeutic Opportunities (Journal of Pharmaceutical Negative Results, 2022)
Neuronal damage results in neuropathy, a condition caused by irregular nerve function in the central or peripheral nervous systems. Since Neuropathic pain shows a heterogeneous profile and is often treated with psychoactive medications, such as benzodiazepines, it presents a great challenge in managing it. A variety of medications are used today to treat Neuropathic pain, including anticonvulsants, opioids, antidepressants, and lidocaine. However, they come with a varieties of side effects. Neuropathic pain needs alternative therapeutics to decrease the adverse effects. In folkloric medicine, Secondary metabolites which includes flavonoids are linked to benzodiazepine receptor affinity, which has been demonstrated in animal studies. Flavonoids have been shown that they reduce neuropathic pain in several animal models A potential role for flavonoids in treating neuritis is demonstrated in this paper. There is increasing evidence that flavonoids may have potential benefits in neuropathic pain. Flavonoids occur naturally in plants and can be found in various dietary sources. The benefits of this therapy have been demonstrated in numerous animal studies, including the reversal of hyperalgesia and allodynia. Neuropathic pain is also alleviated by flavonoids due to their anti-inflammatory effects which is evidenced by lowering multiple pro-inflammatory mediators, like IL-1β, IL-6, TNF-α, and NF-κB. According to preclinical studies, flavonoids may be able to treat neuropathic pain, but human trials are still in the early stages.